Peranan Strategi Pemasaran Produk Fulnadi Dalam Upaya Meningkatkan Penjualan Pada Asuransi Takaful Keluarga Palembang - Sakdiah Sakdiah; Choiriyah Choiriyah (Ekonomica Sharia: Jurnal Pemikiran dan Pengembangan Ekonomi Syariah, 2018)
The focus of research examined in this final project is the role of full-time product marketing strategy in an effort to increase sales of Palembang family takapul insurance. In this study the authors used qualitative research, which describes the data obtained from the field regarding the research problems above. In answering the above problems, this study uses a qualitative descriptive method which is intended to describe or describe the situation or phenomenon as it was at the time of the research, namely presenting data about the marketing strategy of full-blown products by PT Asuransi Takaful Keluarga Palembang Branch. Data collection techniques in this study using observation, interviews and documentation. This research implies that the marketing strategy for full-blown products by PT Asuransi Takaful Keluarga Palembang Branch uses two strategies, namely: First, a strategy which is a strategy for its implementation within the company itself, in terms of improving the quality of human resources for marketers to become professional marketers by conducting research, motivation, and regional evaluation. Second, regional external strategy. Second, the external strategy in its application is carried out by marketers when selling products, such as how to deal with prospective customers, product presentations, good communication and negotiations. The implementation of this strategy in the field has been very effective, as evidenced by the increasing number of full-time customers by PT Asuransi Takaful Keluarga Palembang Branch.